Thermal and Electrochemical Behaviour of Na/Bentonite-Polyaniline Nanocomposite in Different Media - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2010)
The thermal and electrochemical behaviour of the Na/Bentonite-Polyaniline (Na/Bent-PANI) has been investigated by using the thermogravimetric analysis (TGA) and cyclic voltammetry in different media The synthesized Na/Bent-PANI nanocomposites were characterized by using XRD, SEM and electrical conductivity X-ray diffraction and scanning electron microscopy images demonstrated that the polyaniline was inserted into the clay layers According to the thermogravimetric analysis (TGA) while the weight loss of the nanocomposite decreases, with increases bentonite content and the thermal stability of the Na/Bent-PANI is higher than the pure PANI The increase in the bentonite content contributed to the flame retardency and the thermal stability Cyclic voltammetry results showed that electrochemical behaviour of nanocomposites is completely reversible and depends on the media Electrical conductivity of the Na/Bent-PANI nanocomposite was increased together with the temperature and the amount of aniline content
Keywords: Polyaniline; clay nanocomposite; thermal; SEM; Na/Bent; cyclic voltammetry